Gödselbadande hos gris – ett djurvälfärdsproblem? : varför gödselbadar grisar och vilka konsekvenser får det för djurvälfärden och djurskyddslagstiftning? - Söderquist, Astrid (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
Despite the pig’s natural tendency to keep clear of its feces and defecate away from its nesting site, pigs in modern meat production sometimes defecate and urinate in their resting area and lay in their own feces. The purpose of this bachelor thesis was to investigate if this behaviour poses a threat to animal welfare, how it relates to animal welfare legislation, why it occur and to what frequency.